Multi-Factorial Comparison for 24 Distinct Transposition Models for Inclined Surface Solar Irradiance Computation in the State of Palestine: A Case Study - Nassar, Yasser F.; Hafez, Ahmed A.; Alsadi, Samer Y. (Frontiers in Energy Research, 2020)
Solar energy industries region (MENA). Therefore, this article serves two main objectives. Firstly, it compares comprehensively 24 different transposition models. Several statistical methods as Root Mean Square Error (RMSE), Mean Bias Error (MBE) and Percentage Average Deviation (PAD) and t-statistics (t-stat) are used to quantify the performance of the transposition tilted surface models. Furthermore, the transposition models are compared with real measured hourly timeseries data during 15 months (June 2017 to August 2018) for several Palestinian cities (Gaza and Rafah -in Gaza Strip and Herbon, Jericho, Tulkarm and Nablus -in West Bank) to identify the promising and most accurate model. The analysis was carried out on three bases: annually, monthly and clearness index. The transposition models prove their ability to represent the measured data during the annual and monthly based analysis, but they all failed to achieve complacency in the clearness index (Kt) for the clear sky condition (Kt>0.78).HDKR model is considered the most accurate model for depicting the sky diffuse inclined solar irradiance for majority of Palestinian territories. However, for Nablus the Skartveit-Olseth model has require accurate estimation for global solar irradiation particularly on inclined planes. This improves the accuracy of the sizing procedures and optimizes the performance of the solar energy platforms: as photovoltaic modules and flat-plate solar collectors. Variety of the transposition models are developed and reported to determine solar irradiance incident on an inclined surface. However, there is lack in the literature regarding identifying the most promising transposition model particularly for Middle East and North Africa better overall performance than the other candidate models. It even produces 3.4% better than the HDKR model in predicating solar irradiance for inclined plane. Secondly, the article advises simple, reliable and accurate transposition models for the area of MENA for clear sky conditions. The proposed model was tested for the sites under investigation. The proposed model produces significant better performance than the candidate transposition models, as RMSE and PAD values revealed.